Development of Learning Media for Litterature Française Subject Using Articulate Storyline Software 3 - Tengku Ratna Soraya; Nurilam Harianja; Zulherman Zulherman (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
This study aims to develop a learning media for Litterature Française subject using Articulate Storyline Software 3. This study employs the Research and Development (R&D) technique as well as the development ADDIE model, which consists of five stages, there are, Analysis, Design, Development, Implementation, and Evaluation. The data collection instruments used are observation, interviews, and questionnaires. The data analysis technique used is quantitative descriptive statistics. Two experts evaluated Articulate Storyline software 3 learning media products. The results of the assessment by material expert in obtained a score of 90%, that it is classified as a very good category, and media expert obtained a score of 91% that it is classified as a very good category. Thus, Articulate Storyline Software 3 is appropriate to be used as a learning media in Litterature Française subject at French Language Education Program, Faculty of Language and Arts UNIMED.